PENGARUH ADOPSI IAS DAN IFRS TERHADAP RELEVANSI NILAI LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN JASA KEUANGAN YANG TERCATAT DI BEI TAHUN 2008-2013) - Rino Romadhoni; Dyah Purwanti (SUBSTANSI, 2017)
This study aimed to evaluate the adoption of IFRS in Indonesia, related to the goal of increasing the value relevance of financial statements. We used data from the study annual reports and financial reports of 56 financial services company from 2008 to 2013 in the Indonesia Stock Exchange (BEI). We found that the value relevance of financial statements increase from pre-adoption period (2008-2009) to the adoption period (2010-2011), and the value relevance decrease from the period of adoption (2009-2010) to the revision period (2012-2013). Furthermore, we found that adoption of IAS and IFRS affect value relevance of earnings the in the period pre-adoption to period post-adoption. And so adoption of IAS and IFRS affect the relevance of the book value of equity. And overall, this study have shown that the adoption of IAS and IFRS increase value relevance of accounting information in Indonesia.